Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s42003-021-02423-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA released by glycine-auxotrophic Staphylococcus epidermidis small colony variant facilitates catheter-related infections

Abstract: Though a definitive link between small colony variants (SCVs) and implant-related staphylococcal infections has been well-established, the specific underlying mechanism remains an ill-explored field. The present study analyzes the role SCVs play in catheter infection by performing genomic and metabolic analyses, as well as analyzing biofilm formation and impacts of glycine on growth and peptidoglycan-linking rate, on a clinically typical Staphylococcus epidermidis case harboring stable SCV, normal counterpart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…However, more recent studies show that the latter two amino acids auxotrophies are condition-specific regulatory effects, and that carbon catabolite repression stops staphylococci growth in the absence of exogenous proline and arginine when glucose is present in the medium, rather than the lack of biosynthetic pathways [10,11,51]. Glycine auxotrophy has not been reported except in S. epidermidis small colony variants (slow-growing subpopulation of S. epidermidis) [52]. In this study, no amino acid auxotrophy was experimentally observed; model results were consistent with this and, as described previously, the absence of individual amino acids had varying but relatable impacts on experimental and calculated results.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies show that the latter two amino acids auxotrophies are condition-specific regulatory effects, and that carbon catabolite repression stops staphylococci growth in the absence of exogenous proline and arginine when glucose is present in the medium, rather than the lack of biosynthetic pathways [10,11,51]. Glycine auxotrophy has not been reported except in S. epidermidis small colony variants (slow-growing subpopulation of S. epidermidis) [52]. In this study, no amino acid auxotrophy was experimentally observed; model results were consistent with this and, as described previously, the absence of individual amino acids had varying but relatable impacts on experimental and calculated results.…”
Section: Discussionmentioning
confidence: 99%
“…(Table Supplemental Digital Content 1, http://links.lww.com/INF/E930,); half of which were IE, including two cases of IE related to prosthetic valves, which may be attributed to the fact that SCVs tend to form biofilms, leading to infection in prostheses. 4 Moreover, Enterococcus spp. have higher probability of forming biofilms than other bacteria.…”
Section: To the Editorsmentioning
confidence: 99%
“…Staphylococcus epidermidis (SE), a common member of the human skin microbiota, has emerged as an important causative agent of infections related to implanted medical devices ( Post et al, 2017 ; Both et al, 2021 ; Fernández-Rodríguez et al, 2021 ; Liu et al, 2021 ). Infectious lifestyle of this microorganism is supported by phenotype switching from a wild type (WT) to a slow-growing subpopulation characterized by distinctive pathogenic traits and referred to as small colony variants (SCVs) ( Proctor et al, 2006 ; Liu et al, 2021 ). The study of Edwards ( Edwards, 2012 ) demonstrated that this transition occurs via a constitutive mechanism depending upon bacterial replication.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that staphylococcal SCVs, including those produced by SE, can evolve from the WT clone during an infectious process ( Baddour et al, 1988 ; Adler et al, 2003 ; Tuchscherr et al, 2011 , 2016 ; Lin et al, 2016 ; Liu et al, 2021 ). Selection of SCVs is considered a bet-hedging strategy ( Edwards, 2012 ; Liu et al, 2021 ) due to their higher adaptiveness compared to WTs and survival advantage associated with an ability to invade and maintain within host cells ( Magryś et al, 2015 ; Perez and Patel, 2018 ).…”
Section: Introductionmentioning
confidence: 99%